Os caminhos da paixão amorosa e alguns de seus destinos patológicos - Zuanella, Ana Claudia (2016)
This theoretical research came from the interest in studying love passion, mainly in its páthic sense. Starting with its etymology from Classic Greek s word páthos which means passivity and suffering and is also the root of pathology, we used Freudian metapsychology to study some of love passion destinies related to its pathologycal aspects, beginning with the idea that in it, the object in put on the subject´s ideal ego. This gives passion a particular psychic dynamic. We concluded that may there be three kind of love passion: one that gives place to love (endearment), one that finishes with no great damages by self-combustion (catchment) and pathological passion, which destiny is to be prisoner of fixation, excess, pain. We tarried on the third kind of love passion, researching some of its consequences: pathological narcissism, melancholy, lack of otherness, alienation, fetishism.